The Effect of Class C Fly Ash on the Plasticity and Ageing of Ceramic Mixtures Based on Kaolin - Sokolář, Radomír; Nguyen, Martin (MDPI, 2021)
The main aim of the presented article is to describe the behavior of class C fly ash—kaolin plastic doughs during the ageing process. Class C fly ash (CCFA) from the fluidized technology of fuel combustion in a thermal power plant was used as a non-plastic admixture to modify the plasticity in a kaolin–quartz sand mixture (for example, the base of a porcelain mixture). The ageing of plastic ceramic dough determined the effect of the CCFA admixture (0–10–20 wt. %) on the initial water content, plasticity (according to the Pfefferkorn test) and bulk density of a dried green body. The main feature of the CCFA admixture in the kaolin–quartz sand mixture is a solidifying effect. Fly ash increases the initial (mixing) water for the preparation of ceramic dough with constant plasticity (30 mm height of deformed cone Hf, according to the Pfefferkorn test), and Hf increases as the dough ages (the dough solidifies faster and loses its plasticity) with the addition of class C fly ash. The effect of CCFA addition on the plasticity and ageing of kaolin–quartz sand dough is documented on Bigot curves: higher content of fly ash decreases the drying shrinkage of the plastic dough, especially when drying samples that have been aged for 24 h in a plastic wrap (without the possibility of drying). The plastic dough’s ageing increases the porosity of the dried green body with increased content of CCFA in the raw materials mixture and increased ageing time.

The main aim of the presented article is to describe the behavior of class C fly ash—kaolin plastic doughs during the ageing process. Class C fly ash (CCFA) from the fluidized technology of fuel combustion in a thermal power plant was used as a non-plastic admixture to modify the plasticity in a kaolin–quartz sand mixture (for example, the base of a porcelain mixture). The ageing of plastic ceramic dough determined the effect of the CCFA admixture (0–10–20 wt. %) on the initial water content, plasticity (according to the Pfefferkorn test) and bulk density of a dried green body. The main feature of the CCFA admixture in the kaolin–quartz sand mixture is a solidifying effect. Fly ash increases the initial (mixing) water for the preparation of ceramic dough with constant plasticity (30 mm height of deformed cone Hf, according to the Pfefferkorn test), and Hf increases as the dough ages (the dough solidifies faster and loses its plasticity) with the addition of class C fly ash. The effect of CCFA addition on the plasticity and ageing of kaolin–quartz sand dough is documented on Bigot curves: higher content of fly ash decreases the drying shrinkage of the plastic dough, especially when drying samples that have been aged for 24 h in a plastic wrap (without the possibility of drying). The plastic dough’s ageing increases the porosity of the dried green body with increased content of CCFA in the raw materials mixture and increased ageing time.
The Effect of Class C Fly Ash on the Plasticity and Ageing of Ceramic Mixtures Based on Kaolin
Keywords: class C fly ash; plasticity; dough; ageing; bulk density; class C fly ash; plasticity; dough; ageing; bulk density